Technical and economic evaluation of biogas capture and treatment for 'Piedras Blancas' landfill in Córdoba, Argentina - Francisca, Franco Matias (2017)
Landfill gas (LFG) management is one of the most important tasks for landfill operation and closure because of its impact in potential global warming. The aim of this work is to present a case history evaluating an LFG capture and treatment system for the present landfill facility in Cordoba, Argentina. The results may be relevant for many developing countries around the world where landfill gas is not being properly managed. The LFG generation is evaluated by modeling gas production applying the zero order model, Landfill Gas Generation Model (LandGEM - EPA), Scholl Canyon model and triangular model. Variability in waste properties, weather and landfill management conditions are analyzed in order to evaluate the feasibility of implementing different treatment systems. The results show the advantages of capturing and treating LFG in order to reduce the emissions of gases responsible for global warming and to determine the revenue rate needed for the project´s financial requirements. This particular project reduces by half the emission of equivalent tons of CO2 compared with the situation where there is no gas treatment. In addition, the study highlights the need for a change in the electricity prices if it is to be economically feasible to implement the project in the current Argentine electricity market. Implications: Methane has 23 times more greenhouse gas potential than carbon dioxide. Because of that is of great importance to adequately manage biogas emissions from landfills. In addition to that it is environmentally convenient to use this product as an alternative energy source since it prevents methane emissions while prevents fossil fuel consumption minimizing carbon dioxide emissions. Performed analysis indicated that biogas capturing and energy generation implies three times less equivalent carbon dioxide emissions, however a change in the Argentinean electrical market fees are required to guarantee the financial feasibility of the project.